Is the banking stock return affected by exchange, interest, and inflation rates? - Dini Iskandar; Martalena Martalena; Casuarina Putri Benedicta Sihombing; Bram Hadianto (Politeknik Ganesha Medan, 2023)
For public investors, the return becomes the appeal for investors to purchase and sell the stocks in the capital market. Fundamentally, in their analysis, they must consider macroeconomic factors, i.e., foreign exchange, interest, and inflation rates. This study investigates and analyzes these factors as the determinant of stock return. The return intended is owned by the Indonesian capital market-listed banks selected as Kompas 100 Index constituents. Eight years are used as time observation, i.e., from 2015 to 2022. Based on this period, 11 banks exist as the samples. Then, this study utilizes the regression model to analyze the data associated with hypothesis testing. After examining the hypotheses, this study concludes a negative relationship between the exchange rate of IDR/USD on banking stock return: The more weakened the IDR/USD, the lower the stock return. Similarly, this negative sign also happens in the relationship between interest rate and stock return. Conversely, inflation positively affects this return.